KERTAS BUATAN TANGAN (HANDMADE PAPER) DARI LIMBAH SERAI DAPUR - Aprina Murwanti; Yusmini Murdiyah; Ataswarin Oetopo (Institut Seni Indonesia Yogyakarta, 2021)
Kitchen Lemongrass (Cymbopogon Citratus) waste has the potential to become a strong and environmentally-friendly material for handmade paper due to its high cellulose content, distinctive texture and aroma. So far, handmade paper made from kitchen lemongrass waste is made in Thailand and India and is available in the international market. Indonesia, which has quite high lemongrass resources, has not explored much lemongrass waste in the exploration of handmade paper. Although it has good potential as a handmade paper material, lemongrass waste must be mixed with kapok fiber and processed with the right composition and process to produce handmade paper that is strong but foldable and not easily torn. The methods of observation, experimentation and documentation were carried out in this study to achieve adequate results for work. The various stages ranging from waste preparation to printing, boiling, pulping, filtering, printing and drying are presented in this scientific article to open up the possibility of further research into process of handmade lemongrass wastepaper that environmentally friendly. Limbah serai dapur (Cymbopogon citratus) memiliki potensi untuk menjadi bahan baku kertas buatan tangan (handmade paper) yang kuat dan ramah lingkungan karena kandungan selulosa yang tinggi serta tekstur dan aromanya yang khas. Selama ini, kertas buatan tangan yang terbuat dari limbah serai dapur dibuat di Thailand dan India dan tersedia di pasar internasional. Indonesia yang memiliki sumber daya serai yang cukup tinggi, belum banyak mengeksplorasi limbah serai dalam eksplorasi kertas buatan tangan. Meskipun memiliki potensi yang baik sebagai bahan kertas buatan tangan, limbah serai harus dicampur dengan serat kapuk dan diolah dengan komposisi dan proses yang tepat untuk menghasilkan kertas buatan tangan yang kuat namun dapat dilipat dan tidak mudah robek. Metode observasi, eksperimentasi, dan dokumentasi dilaksanakan dalam penelitian ini untuk mencapai hasil yang memadai untuk berkarya. Berbagai tahapan mulai dari persiapan limbah hingga pencetakan, perebusan, pembuatan bubur (pulp), penyaringan, pencetakan, dan penjemuran disampaikan di dalam artikel ilmiah ini untuk membuka kemungkinan penelitian lanjutan dalam proses kertas limbah serai buatan tangan yang ramah lingkungan.